Response of the Endophytic Diazotroph Gluconacetobacter diazotrophicus on Solid Media to Changes in Atmospheric Partial O(2) Pressure - Pan, Bo (American Society for Microbiology, 2001)
Gluconacetobacter diazotrophicus is an N(2)-fixing endophyte isolated from sugarcane. G. diazotrophicus was grown on solid medium at atmospheric partial O(2) pressures (pO(2)) of 10, 20, and 30 kPa for 5 to 6 days. Using a flowthrough gas exchange system, nitrogenase activity and respiration rate were then measured at a range of atmospheric pO(2) (5 to 60 kPa). Nitrogenase activity was measured by H(2) evolution in N(2)-O(2) and in Ar-O(2), and respiration rate was measured by CO(2) evolution in N(2)-O(2). To validate the use of H(2) production as an assay for nitrogenase activity, a non-N(2)-fixing (Nif(−)) mutant of G. diazotrophicus was tested and found to have a low rate of uptake hydrogenase (Hup(+)) activity (0.016 ±  0.009 μmol of H(2) 10(10) cells(−1) h(−1)) when incubated in an atmosphere enriched in H(2). However, Hup(+) activity was not detectable under the normal assay conditions used in our experiments. G. diazotrophicus fixed nitrogen at all atmospheric pO(2) tested. However, when the assay atmospheric pO(2) was below the level at which the colonies had been grown, nitrogenase activity was decreased. Optimal atmospheric pO(2) for nitrogenase activity was 0 to 20 kPa above the pO(2) at which the bacteria had been grown. As atmospheric pO(2) was increased in 10-kPa steps to the highest levels (40 to 60 kPa), nitrogenase activity decreased in a stepwise manner. Despite the decrease in nitrogenase activity as atmospheric pO(2) was increased, respiration rate increased marginally. A large single-step increase in atmospheric pO(2) from 20 to 60 kPa caused a rapid 84% decrease in nitrogenase activity. However, upon returning to 20 kPa of O(2), 80% of nitrogenase activity was recovered within 10 min, indicating a “switch-off/switch-on” O(2) protection mechanism of nitrogenase activity. Our study demonstrates that colonies of G. diazotrophicus can fix N(2) at a wide range of atmospheric pO(2) and can adapt to maintain nitrogenase activity in response to both long-term and short-term changes in atmospheric pO(2).